Managing the starry ray (Raja asterias) in the mid-western Adriatic Sea: why sex matters in fisheries conservation - Bargione, Giada; Pardini, Andrea; Donato, Fortunata; Veli, Daniel Li; Sabatini, Laura; Sepe, Emily; Scarcella, Giuseppe; Lucchetti, Alessandro (Frontiers in Marine Science, 2025)
The starry ray, Raja asterias (Delaroche 1809), is a demersal Mediterranean skate often caught as bycatch in bottom trawls and set nets. Due to high fishing pressure in the Adriatic Sea, key life history traits were investigated to support effective conservation and fishery management. Specimens were collected from 2019 to 2023 through both fishery-dependent and independent sampling in the mid-western Adriatic. Age was estimated for the first time in cartilaginous fish using burnt and dissected vertebrae. The reproductive cycle was assessed through macroscopic gonad examination, while spatial distribution was analyzed in relation to sex and maturity (mature vs immature). Trends in relative abundance and biomass (2007–2024) were evaluated using standardized survey data. Results revealed significant sexual dimorphism in biological traits. Females showed a broader size range (170–590 mm vs 160–505 mm), greater disc width (115–410 mm vs 105–342 mm), and positive allometric growth, compared to isometric growth in males. Growth patterns also differed: Von Bertalanffy parameters were L∞ = 724, k = 0.28 for females and L∞ = 574, k = 0.44 for males. Females reached greater maximum age (4.5 vs 4.0 years), and achieved sexual maturity at larger sizes (425 vs 360 mm) and older ages (approx. 3.0 vs 2.0 years). Spatial analysis showed that immature individuals are concentrated nearshore (<50 m depth), while mature ones inhabit deeper waters (up to 80 m). During the reproductive season, adults migrate inshore, overlapping with immature habitats. Abundance and biomass indices significantly increased over time, particularly after 2020. These findings underscore the need for sex-specific biological parameters in management strategies. Conservation measures should avoid using population-wide averages and instead adopt the most precautionary approach. Additionally, limiting fishing in shallow waters could reduce bycatch of immature or egg-laying individuals for much of the year, positively impacting population recovery.